Maize/ Joint Velch Intercropping and N Fertilization Effects on Striga Infestation and Maize Grain Yield in the Southern Guinea Savanna of Nigeria - M.S, Bassey; P. A, Ibrahim; Mohammed, Mohammed; k, A.; Isah, Musa; A.B, Hadiza; E.N, Ngonadi (International Journal of Environment, Agriculture and Biotechnology, 2019)
The parasitic weed Striga poses a serious threat to cereal production in sub-Saharan Africa. For many years, technological packages for the control of this weed were proposed and implemented on farmers’ fields. A study was conducted in 2012 and 2013 to determine maize/ Jointvetch (Aeschynomenehistrix) and N fertilization effect on Striga infestation and maize yield. The intercropping trial consists of six treatments, four inorganic N fertilizer levels of 0, 60, 90, 120 kg ha-1, alternate hill and same hill intercropping of A. histrix. The experiment was laid out in a randomized complete block design with three replicates. Alternate hill and same hill intercropping significantly (P < 0.05) reduced Striga infestation with respect to Striga shoots per m-2 and plot, Strigareation score and enhanced maize grain yield. There was a significant decline in the level of damage by Striga on maize in plots that received 60 – 120 kg N ha-1. Alternate hill and same hill intercropping had maize grain yield of 3295 kg ha-1 and 2616 kg ha-1 which were significantly higher than those obtained without inorganic N application (306 kg ha-1). Inorganic N application had a significant (P < 0.05) effect on grain yield. Lowest grain yield of 306 kg ha-1 was obtained without inorganic N application, which was significantly (P<0.05) different from those fertilized with inorganic N, that had comparable grain yields. Inorganic N fertilizer rate of 60 kg ha-1 seems to be optimum for maize.